2010 International Conference on Body Sensor Networks 2010
DOI: 10.1109/bsn.2010.36
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Close-Proximity RSSI-Based Tracking in Wireless Sensor Networks

Abstract: Abstract-In this paper we develop a continuous high-precision tracking system based on Received Signal Strength Indicator (RSSI) measurements for small ranges. The proposed system uses minimal number of sensor nodes with RSSI capabilities to track a moving object in close-proximity and high transmission rate. The close-proximity enables conversion of RSSI measurements to range estimates and the high transmission rate enables continuous tracking of the moving object. The RSSI-based tracking system includes cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In order to achieve accurate positioning with WSN, a large number of localization algorithms are established, such as (Blumrosen, Hod, Anker, Dolev, & Rubinsky, 2010;Wang, Jia, Lee & Li, 2003;Seidel & Rapport, 1992;Smailagic & Kogan, 2002;Bahl & Padmanabban, 2000;Seidel & Rappaport, 1991;Hightower, Want & Boriello, 2000). The distance between sensor nodes can be simply estimated according signal strength consumption.…”
Section: Distance Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to achieve accurate positioning with WSN, a large number of localization algorithms are established, such as (Blumrosen, Hod, Anker, Dolev, & Rubinsky, 2010;Wang, Jia, Lee & Li, 2003;Seidel & Rapport, 1992;Smailagic & Kogan, 2002;Bahl & Padmanabban, 2000;Seidel & Rappaport, 1991;Hightower, Want & Boriello, 2000). The distance between sensor nodes can be simply estimated according signal strength consumption.…”
Section: Distance Estimationmentioning
confidence: 99%
“…A variant of the fingerprint method (Sun, Lang, Wang & Liu, 2014) interpolates the measured data to give a better fitting on a RSSI value. Advanced statistical and signal processing methods to mitigate channel distortion and packet loss are utilized to achieve tracking resolution of few centimeters (Blumrosen, Hod, Anker, Dolev & Rubinsky, 2010). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose to estimate the solution to the criterion in Equation (2) by using two stages similar to [30,35]: first to approximate the range between the mobile nodes and the N anchor nodes for Q measurements interval; and then to apply geometric and statistical methods on the range approximations to obtain the instant location. Consequently, the MMSE criterion can be refined to two sub-criterions, estimation of the range between the sensor nodes, and then the estimate the location based on the range estimations: trueg^=argmingE[Dg(Pr)]2 truev^=argminvE[Lv(D^)]2s.t.|Li+1Li|<δ,where g is the transformation that operates on the power measurements matrix P r and its output is set of range estimations between the mobile node and the anchor nodes, v is the transformation that operates on the range estimations, and D̂=ĝ(p r ) is a N × K matrix of approximated distances between the mobile nodes and the N anchor nodes over K measurements.…”
Section: Rssi Based Tracking Of a Body Segmentmentioning
confidence: 99%
“…This has caused RSSI-based tracking to not be a viable solution for the motion tracking problem as it requires much higher accuracy. However, Blumrozen et al [17] suggested and showed that under certain conditions, RSSI can be a valid solution for the human motion tracking problem.…”
Section: Domain Specific Assumptionsmentioning
confidence: 99%